Predicting the variation of stacking fault energy for binary Cu alloys by first-principles calculations. (15th September 2020) - Cai, T.; Li, K.Q.; Zhang, Z.J.; Zhang, P.; Liu, R.; Yang, J.B.; Zhang, Z.F.
Abstract: The variation of stacking fault energy (SFE) in a number of binary Cu alloys is predicted through considering the Suzuki segregation by the full potential linearly augmented plane wave (FPLAPW) method. The calculated results show that some solute atoms (Mg, Al, Si, Zn, Ga, Ge, Cd, Sn, and Pb), which prefer to form the Suzuki segregation, may decrease the value of SFE; while the others (Ti, Mn, Fe, Ni, Zr, Ag, and Au), which do not cause the Suzuki segregation may not decrease the SFE. Furthermore, it is interesting to find that the former alloying elements are located on the right of Cu group while the latter on the left of Cu group in the periodic table of elements. The intrinsic reasons for the new findings can be traced down to the valences electronic structure of solute and Cu atoms, i.e., the similarity of valence electronic structure between solute and Cu atoms increases the value of SFE, while the difference decreases the value of SFE.